An economic evaluation of pharmacopuncture versus usual care for chronic neck pain: a pragmatic randomized controlled trial - Doori Kim; Eun-San Kim; Hyun Jin Song; Sun-Young Park; Kyoung Sun Park; Yoon Jae Lee; In-Hyuk Ha (BMC, 2023)
Abstract Background This study aimed to evaluate the cost utility of pharmacopuncture in comparison with usual care for patients with chronic neck pain. Methods A 12-week, multicenter, pragmatic randomized controlled trial was conducted, and 101 patients suffering from chronic neck pain for more than six months were randomly placed into the pharmacopuncture and usual care groups to receive four weeks of treatment and 12 weeks of follow-up observations. The quality-adjusted life year (QALY) was calculated using EQ-5D and SF-6D. Concerning costs in 2019, a primary analysis was performed on societal perspective cost, and an additional analysis was performed on healthcare perspective cost. Results Compared to usual care, pharmacopuncture was superior as it showed a slightly higher QALY and a lower incremental cost of $1,157 from a societal perspective. The probability that pharmacopuncture would be more cost-effective at a willingness-to-pay (WTP) of $26,374 was 100%. Pharmacopuncture was also superior from a healthcare perspective, with a lower incremental cost of $26. The probability that pharmacopuncture would be more cost-effective at a WTP of $26,374 was 83.7%. Conclusions Overall, pharmacopuncture for chronic neck pain was found to be more cost-effective compared to usual care, implying that clinicians and policy makers should consider new treatment options for neck pain. Trial registration Number NCT04035018 (29/07/2019) Clinicaltrials.gov; Number KCT0004243 (26/08/2019) Clinical Research Information Service.